ALLELOPATHIC EFFECT OF ROOT EXUDATES FROM SOME SUNFLOWER CULTIVARS ON ACCOMPANYING WEEDS - Alaa A. J. AL-Behadili (The Iraqi Journal of Agricultural science)
The study looked at what happened to the weeds growth in the field when different types of sunflowers released root exudates grown in the summer of 2023. The goal was to determine if sunflower types' allelopathic potential affects weed growth and number. The results showed that after 30, 60, 90, and 120 days of cultivation, the Flamme cultivar did better than the Sakha, Aqmar, and Abba5 cultivars in reducing the number of weeds and their dry weight. The weed density dropped by 60%, 46%, 38%, and 35% compared to the control treatment, and the weeds' dry weight dropped by 61%, 66%, 62%, and 53% compared to the control treatment, in that order. The Sakha and Aqmar cultivars were next. The Abba5 cultivar recorded the lowest reduction in the number of weeds and their dry weights. We used the staircase experiment method to get rid of any competition when we tested the allelopathic potential of the fluids from the Flamme and Sakha cultivars. The Flamme cultivar's root exudates were found to be better at stopping the growth and dry weight of wild beet and purple panic weed than the Sakha cultivar's root exudates. The high-performance liquid chromatography test revealed that the Flamme and Sakha cultivars' root exudates had nine different compounds. The amounts of these phenolic compounds varied between the two studied cultivars. Most of the isolated compounds were found in higher amounts in the Flamme cultivar than in the Sakha cultivar. Most of the isolated compounds are known to stop plants, even weeds, from sprouting and growing naturally.